Analyzing the ambitions of renewable energy policy in the EU and its Member States. (September 2021) - Strunz, Sebastian; Lehmann, Paul; Gawel, Erik
Abstract: This paper investigates whether the EU's governance framework facilitates an ambitious transition to renewable energy sources (RES) in the EU and its Member States. First, we propose a comprehensive concept of ambition based on targets, target achievement and enforcement procedure. Second, we analyze empirical evidence regarding these aspects for RES policy in the EU. In particular, Member States' progress towards the 2020 RES targets suggests a modest effect of the EU governance framework on national RES ambitions. Instead, national RES expansion trajectories seem to be strongly path-dependent. Meanwhile, frontrunner Member States' over-achievements enable the EU to close in on its 2020 target. Highlights: Comprehensive conceptual framework of ambition. Empirical analysis of renewable energy policy within EU multilevel governance. Thorough synthesis of the current status of renewable energy target achievement in the EU. Member States' RES deployment trajectories seem to be strongly path-dependent.